PENGEMBANGAN PARIWISATA KHUSUS (NICHE TOURISM) MELALUI PENYELENGGARAAN EVENT KEBUGARAN (WELLNESS TOURISM) DI UBUD Studi Kasus Bali Spirit Festival 2019 - Permatasari, Dwi Novita Cahyaningtyas (Jurusan Pariwisata Politeknik Negeri Kupang, 2021)
Tourism during the Fordist era displayed the characteristics of mass tourism, while post-Fordist tourism provided alternative tourism characteristics, namely niche tourism. Today contemporary tourism has both the characteristics of mass and niche tourism. This research answers two questions on motivation of niche tourist towards tourist satisfaction and revisit intention, and how to develop niche tourism through wellness events. This research used qualitative research method. Motivation in this study is divided into push and pull factors. The push factors for yoga tourism in Bali include Experience & Personal Development, Interpersonal, and Prestige & Benefits, while the pull factors are Community, Atmosphere & Climate, Safety & Hygiene, Accessibility, Price & Service Availability, Culture & Ethnic. The majority of visitors are satisfied with the service and quality of the event and have the intention to revisit Bali Spirit Festival in the following year. Finally, the development of special tourism through wellness tourism events can be done within market segmentation and developing tourism package clusters